Training, taper and recovery strategies for effective competition performance in judo - Papacosta, E. (2015)
Post-exercise carbohydrate-protein consumption and tapering periods during training periodisation have been proposed as effective recovery strategies in several sports; however, limited attention has been given to judo. Apart from training and recovery, effective competition performance can also be influenced by several stimuli on the competition day, which may be manifested as distinct endocrine responses. The main objective of this thesis was to influence effective competition performance in judo, through examining strategies that can aid recovery from intense exercise/training and examining endocrine responses to competition. Three experimental studies on recovery were completed (chapters 3-5) followed by an observational study on a judo competition day (chapter 6) in elite, national level, male judo athletes. Studies 1 and 2 examined the effects 1000 ml of post-exercise chocolate milk (CM) consumption compared with water (W) following an intense judo training session (chapter 3) and five days of intense judo training with concomitant weight loss (chapter 4) on the recovery of salivary cortisol (sC), salivary testosterone (sT), salivary testosterone:cortisol (sT/C) ratio, salivary secretory IgA (SIgA) absolute concentrations and secretion rate, muscle soreness, mood state and judo-related performance. Study 1 (n=10) did not show any beneficial effects of acute CM consumption on aspects of recovery of any of the measured variables, except for a lower perception of soreness (p<0.05) and a tendency for better push-up performance (p=0.09). Study 2 (n=12) showed that post-exercise CM consumption resulted in significantly lower sC levels, a tendency for higher sT/C ratio (p=0.07), better judo-related performance, lower muscle soreness and reduced mood disturbance (p<0.05) with W. In addition, post-exercise consumption of CM resulted in a 1.1% decrease in body weight, indicating that CM is an effective recovery beverage during periods of intense judo training without affecting intentional weight loss. Study 3 (n=11) examined the effects of a 2-week exponential taper following 2 weeks of intense judo training on recovery of the aforementioned variables. Within 12 days of tapering there were evidence of enhanced performance, lower sC, higher sT and higher sT/C ratio, higher SIgA secretion rate, lower muscle soreness and reduced mood disturbance, indicating that a tapering period of ~10 days is an effective recovery strategy for optimising judo performance. Study 4 observed the responses of sC, sT, SIgA absolute concentrations and SIgA secretion rate and self-measured anxiety state in the winners (n=12) and losers (n=11) of a judo competition. Winners presented significantly higher morning sC levels and higher cognitive anxiety in anticipation of the competition, as well as a tendency for higher SIgA secretion rate (p=0.07) and significantly higher saliva flow rate mid-competition. These findings indicate that winners experienced higher arousal levels and that anticipatory sC might have some predictive value for winning performance in judo. This thesis concludes that nutrition and tapering are both important aspects of effective recovery; CM can be an effective nutritional recovery aid during periods of intense judo training and tapering for 7-12 days can optimise judo performance and can be implemented prior to competitions. In addition, elevated sC levels in anticipation of a judo competition and higher levels of arousal could have some predictive value for winning performance in judo. Further research could focus on strategies to increase levels of arousal in anticipation of competition.